2014
DOI: 10.1063/1.4882297
|View full text |Cite
|
Sign up to set email alerts
|

Heating mode transition in a hybrid direct current/dual-frequency capacitively coupled CF4 discharge

Abstract: Computer simulations based on the particle-in-cell/Monte Carlo collision method are performed to study the plasma characteristics and especially the transition in electron heating mechanisms in a hybrid direct current (dc)/dual-frequency (DF) capacitively coupled CF4 discharge. When applying a superposed dc voltage, the plasma density first increases, then decreases, and finally increases again, which is in good agreement with experiments. This trend can be explained by the transition between the four main hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
10
1
1
Order By: Relevance
“…This means an auxiliary DC discharge at chamber center will give rise to a lot of ionization and the nonlinear enhancement of electron density in the bulk. This process may be similar to the seed electron effect of atmosphere atmospheric discharge [43] and the density enhancement effect in DC superposed CCP discharge [44][45][46][47][48]. Kawamura et al [41,49] and Zhang et al [47] reported simulation results of DC superposed CCP discharge, and found that DC discharge can significantly improve electron density, which is consistent with the experimental phenomenon of our experiment.…”
Section: Dc+rf Hybrid Dischargesupporting
confidence: 91%
“…This means an auxiliary DC discharge at chamber center will give rise to a lot of ionization and the nonlinear enhancement of electron density in the bulk. This process may be similar to the seed electron effect of atmosphere atmospheric discharge [43] and the density enhancement effect in DC superposed CCP discharge [44][45][46][47][48]. Kawamura et al [41,49] and Zhang et al [47] reported simulation results of DC superposed CCP discharge, and found that DC discharge can significantly improve electron density, which is consistent with the experimental phenomenon of our experiment.…”
Section: Dc+rf Hybrid Dischargesupporting
confidence: 91%
“…此外, 一 些研究还表明裁剪波形可以调控放电中中性成分 的密度 [124] . 除了单纯的裁剪波导致的电非对称效 应, 电非对称效应与几何非对称效应 [125−127] 以及 磁非对称效应的耦合等 [14,16,128] 均逐渐被提出及研 究, 开展并深入相关的研究能够为加深对CCP放 电过程的理解以及更好地实现对实际工艺中等离 子体参数的控制提供很大的帮助.…”
Section: 总之 近些年的大量研究都表明利用裁剪波形unclassified
“…They found that the electric field in the plasma bulk is striated and electrons are accelerated within these striated fields when some certain conditions are met in CF 4 gas discharges. Indeed, lots of related numerical [23,24] and experimental [25,26] studies have been focused on the electron heating mechanisms in both electronegative or electropositive CCPs, for which, the discharge modes and mode transitions [27][28][29] dependent on different external parameters are always studied as the important considerations. Generally, at low pressures or voltages, the discharge is always sustained in α-mode and would transfer to be in γ-mode with increasing pressure and voltage.…”
Section: Introductionmentioning
confidence: 99%